"Life mapping" exploring the lived experience of COVID-19 on access to HIV treatment and care in Malawi [version 2; peer review: 2 approved] - Ruby T. Zolowere; Jane Harries; Krista Lauer; Khokhelwa Zokwana; Solange L. Baptiste; Jelena Bozinovski (Gates Open Research)
Background The COVID-19 pandemic in Malawi exacerbated, existing public health challenges including access to HIV treatment and care services. “Life Mapping,” a component of the Citizen Science community-led project in Malawi, documented the lived experiences and perspectives of people living with HIV in the context of COVID-19. Methods Citizen Science Life Maps is a three-year qualitative, longitudinal project utilizing collaborative and participatory research methods through digital storytelling to document peoples’ daily lives. Twenty participants living with HIV were recruited between 2022 and 2023 in two central regional districts of Malawi and two urban areas. The participants were given mobile smart phones to document the impact of COVID-19 on HIV prevention and treatment services, HIV treatment literacy, mental health and the COVID -19 vaccine. Data was analyzed using a thematic analysis approach. Results Access to HIV prevention and treatment slowly recovered yet introducing multi-month anti- retroviral dispensing raised concerns. In the absence of mental health care services, participants were resourceful in seeking alternative ways to deal with mental health. However, state sponsored violence in relation to COVID-19 public health measures impacted negatively not only on mental well-being but also on HIV treatment adherence. Whilst most recognized the importance of the COVID-19 vaccine, especially for people living with HIV, myths, misinformation, and conspiracy theories around the vaccine persisted especially religious themed misinformation. Conclusions The relationship between misinformation and COVID-19 vaccine hesitancy is complex and medical and scientific approaches may not be sufficient to prevent misinformation. Fear and misinformation are likely attributed to global uncertainty during the pandemic and the speed at which vaccines were developed with minimal opportunity to prepare global communities.